2014
DOI: 10.1111/1758-2229.12132
|View full text |Cite
|
Sign up to set email alerts
|

Broad Escovopsis‐inhibition activity of Pseudonocardia associated with Trachymyrmex ants

Abstract: Attine ants maintain an association with antibiotic-producing Actinobacteria found on their integuments. Evidence supports these bacteria as auxiliary symbionts that help ants to defend the fungus gardens against pathogens. Using Pseudonocardia strains isolated from Trachymyrmex ants, we tested whether the inhibitory capabilities of such strains are restricted to Escovopsis parasites that infect gardens of this ant genus. Twelve Pseudonocardia strains were tested in in vitro bioassays against Escovopsis strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…These observations suggest that Pseudonocardia symbionts do not seem to play a prominent role in A. texana (at least in foundress queens or incipient nests). Whereas Pseudonocardia occur in high abundances in the integumental accretions of Trachymyrmex and Acromyrmex workers and queens (Currie et al ., ; Fernández‐Marín et al ., ; Andersen et al ., ; Meirelles et al ., ), the diversity and abundance of Pseudonocardia types associated with A. texana in our study seem to resemble the kind of diversity found in environmental sources, as for example soil.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These observations suggest that Pseudonocardia symbionts do not seem to play a prominent role in A. texana (at least in foundress queens or incipient nests). Whereas Pseudonocardia occur in high abundances in the integumental accretions of Trachymyrmex and Acromyrmex workers and queens (Currie et al ., ; Fernández‐Marín et al ., ; Andersen et al ., ; Meirelles et al ., ), the diversity and abundance of Pseudonocardia types associated with A. texana in our study seem to resemble the kind of diversity found in environmental sources, as for example soil.…”
Section: Resultssupporting
confidence: 76%
“…S3). Pseudonocardia can reside in accretions on the integument of many genera of fungus‐growing ants (Currie et al ., ; Fernández‐Marín et al ., ), particularly in the genera Acromyrmex (sister clade to Atta ) and Trachymyrmex (Currie et al ., ; Fernández‐Marín et al ., ; Meirelles et al ., ). Such integumental accretions are not visible in Atta species, and previous studies indicated that integumental Pseudonocardia were absent or rare in Atta species (Currie et al ., ; Fernández‐Marín et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, Meirelles et al . () found several novel strains of Pseudonocardia isolated from previously unidentified Trachymyrmex s.l. species, several of which can now be identified as M. atlanticus .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, few studies to date have included actinobacteria, which grow in cuticular crypts on the ants' integuments (Currie et al, 1999b;Currie, 2001;Currie et al, 2003c;Currie et al, 2006;Cafaro et al, 2011), isolated from Mycetomoellerius species. However, Meirelles et al (2014) found several novel strains of Pseudonocardia isolated from previously unidentified Trachymyrmex s.l. species, several of which can now be identified as M. atlanticus.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation